Moral development as the influencer of fraud detection - Heliantono, Heliantono; Gunawan, Itjang D.; Khomsiyah, Khomsiyah; Arsjah, Regina J. (International Journal of Financial, Accounting, and Management, 2020)
Purpose: The purpose of the study is to analyze the influence of the external auditor's moral development, continuing professional education (CPE) on fraud, and education on fraud detection. Research Methodology: The research sample was taken randomly, and the total respondents were 171 external auditors working in public accounting firms in Indonesia. The analytical data method uses multiple linear regression. The instrument measures moral development using three scenarios, which are the auditor opinion, allowance for receivables, and cost reimbursement, with modifications made to conform with Law 5/2011 concerning public accountant. Results: Results found that moral development and education had a significant effect on fraud detection, while CPE on fraud has no effect on fraud detection. Limitations: One newly developed of the three scenarios measuring moral development may not be suitable for region other than Indonesia. Contribution: The accounting red flag dimension is the dimension that has the most attention, while the dimension according to SA 240, the perpetrator dimension, is the dimension that has the least attention. Keywords: Kohlberg moral development, Education, CPE on fraud, Fraud detection